The Effect Of Methods Of Controling Drug Drinking On The Compiance Of Mothera Consuming FE Tablets In Pregnat Women - Fitriani; Tenriwati; Rusnawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
Disobedience of pregnant women to consume Fe tablets and lack of knowledge of the importance of iron tablets during pregnancy are factors that can cause anemia. Non-compliance occurs because pregnant women feel nauseous due to the taste and smell of Fe tablets, in addition to the lack of knowledge of mothers about the importance of consuming Fe tablets so that pregnant women feel no need to consume them. So it is necessary to monitor the consumption of iron tablets (fe) by using the method of supervising the consumption of iron tablets. The purpose of this study was to determine the effect of the drug-taking supervision method on the compliance of pregnant women suffering from anemia in the working area of ​​the Borong Rappoa Public Health Center, Kindang District, Bulukumba Regency. This research is a quantitative study with a pre-experimental research design using the one-group pretest-posttest design method. Data were collected using a check sheet for consuming iron tablets (FE). The population in this study were all pregnant women suffering from anemia in the working area of ​​the Borong Rappoa Public Health Center, Kindang District, Bulukumba Regency, for the period from January to March 2019 as many as 65 mothers. The sample in this study were mothers in the working area of Borongrappoa Health Center as many as 15 people. The results of the study used the Mc Nemer test with a significance value of p = 0.16. The results were obtained that before being given the drug-taking supervisory method (PMO), most of the pregnant women did not comply with taking Fe tablets as many as 10 people (66.7%) and 5 people obeyed (33.3%). Meanwhile, after being given the drug-taking supervisor method (PMO) the highest category was in the obedient category as many as 12 people (80%), and in the non-adherent category as many as 3 people (20%), so the p-value = 0.016 <0.05 which means there is a difference in the proportion before and after the administration of the drug-taking supervisory method (PMO) in consuming Fe tablets to pregnant women in the working area of ​​the Borong Rapoa Public Health Center.